Aumône et mendicité : un autre regard sur la question des talibé au Sénégal - Papa Oumar Ndiaye (Cahiers de la Recherche sur l'Education et les Savoirs)
The repeated failure of policies fighting against talibé children’s begging implemented by the Senegalese government leads one to wonder why there is no improvement to the situation despite all the effort devoted to the issue by the government with the support of the civil society and international agencies. This work attempts to answer the question by putting forward a hypothesis that provides key elements to understanding the issue. In fact, a study conducted in a specific suburb of Dakar shows that Talibé’s begging fulfills a real social function, allowing donors to carry out the duty of charity, a duty particularly important since urban life leaves little time for Muslim rites. This conclusion constitutes a major contribution to the ongoing debate on the talibé issue that remains chiefly informed by a theory of legal interpretation aiming to protect children which provides an analysis that only takes into account actors such as parents/Koran teachers/children, leaving out the charity “market” context.